Towards Gender Equality in the Music Industry: Education, Practice and Strategies for Change - Strong, Catherine; Raine, Sarah (Bloomsbury Publishing USA, 2019)
Gender inequality is universally understood to be a continued problem in the music industry. This volume presents research that uses an industry-based approach to examine why this gender imbalance has proven so hard to shift, and explores strategies that are being adopted to try and bring about meaningful change in terms of women and gender diverse people establishing ongoing careers in music. The book focuses on three key areas: music education; case studies that explore practices in the music industry; and activist spaces. Sitting at the intersection between musical production, the creative industries and gender politics, this volume brings together research that considers the gender politics of the music industry itself. It takes a global approach to these issues, and incorporates a range of genres and theoretical approaches. At a time when more attention than ever is being paid to gender and music, this volume presents cutting edge research that contributes to current debates and offers insights into possible solutions for the future.
Keywords: Music / Business Aspects; Music / Philosophy & Social Aspects; Social Science / Gender Studies; Social Science / Women's Studies

Beyond the Dance Floor: Female DJs, Technology and Electronic Dance Music Culture - Farrugia, Rebekah (Intellect Books, 2012)
A pathbreaking study of the women who create electronic dance music, Beyond the Dance Floor focuses on the largely neglected relationship between these women and the conceptions of gender and technology that continue to inform the male-dominated culture surrounding electronic music. In this volume, Rebekah Farrugia explores a number of important issues, including the politics of identity and representation, the bonds formed by women within the DJ community and the role female DJs and producers play in this dance music culture as well as in the larger public sphere. Though Farrugia primarily focuses on women's relationship to music-related technologies – including vinyl, mp3s and digital production software – she also deftly extends her argument to the strategic use of the Internet and web design skills for purposes tied to publicity, networking and music distribution.
Keywords: Music / Genres & Styles / Electronic; Performing Arts / Dance / General; Social Science / Popular Culture; Social Science / Women's Studies; Technology & Engineering / General

The Lost Women of Rock Music: Female Musicians of the Punk Era - Reddington, Helen (Equinox Pub., 2012)
In the late 1970s and early 1980s a new phenomenon emerged in UK popular music - female guitarists, bass-players, keyboard-players and drummers began playing in bands. Before this time, women's presence in rock bands, with a few notable exceptions, had always been as vocalists. This sudden influx of female musicians into the male domain of rock music was brought about by the enabling ethic of punk rock ('anybody can do it ') and by the impact of the Sex Discrimination Act. With the demise of the punk scene, interest in these musicians evaporated and other priorities became important to music audiences. This book investigates the social and commercial reasons why these women became lost from the rock music record, and rewrites this period of popular music history. In addition to a wealth of original interview material with key protagonists, including the late John Peel, Geoff Travis, The Raincoats and Poison Girls, this new edition has been updated to include interviews with members of Birmingham-based band The Au Pairs, Leeds-based band Delta 5 and Viv Albertine of The Slits. Lucy Whitman (aka Lucy Toothpaste), who started the fanzine Jolt and later wrote for Spare Rib, also provides enlightening words on the relationship between female punk band members and feminism. The author also draws on her own experience as bass-player in a punk band.
Keywords: Music / Genres & Styles / Punk; Music / History & Criticism; Social Science / Women's Studies

The Aftermath of Feminism: Gender, Culture and Social Change - McRobbie, Angela (SAGE Publications, 2009)
Congratulations to Dr. McRobbie! This book has been named to the list of books for the 2009 Critics Choice Book Award of the American Educational Studies Association (AESA).These essays show Angela McRobbie reflecting on a range of issues which have political consequence for women, particularly young women, in a context where it is frequently assumed that progress has been made in the last 30 years, and that with gender issues now 'mainstreamed' in cultural and social life, the moment of feminism per se is now passed. McRobbie trenchantly argues that it is precisely on these grounds that invidious forms of gender -re-stabilisation are able to be re-established. Consumer culture, she argues, encroaches on the terrain of so called female freedom, appears supportive of female success only to tie women into new post-feminist neurotic dependencies. These nine essays span a wide range of topics, including - the UK government's 'new sexual contract' to young women, - popular TV makeover programmes, - feminist theories of backlash and the 'undoing' of sexual politics, - feminism in a global frame- the 'illegible rage' underlying contemporary femininities.
Keywords: Social Science / Essays; Social Science / Feminism & Feminist Theory; Social Science / Sociology / General; Social Science / Women's Studies

Pretty in Punk: Girls' Gender Resistance in a Boys' Subculture - Leblanc, Lauraine (Rutgers University Press, 1999)
Pretty in Punk combines autobiography, interviews, and sophisticated analysis to create the first insider's examination of the ways punk girls resist gender roles and create strong identities.Why would an articulate, intelligent, thoughtful young women shave off most of her hair, dye the remainder green, shape it into a mohawk, and glue it onto her head? What attracts girls to male-dominated youth subcultures like the punk movement? What role does the subculture play in their perceptions of themselves, and in their self-esteem? How do girls reconcile a subcultural identity that is deliberately coded “masculine” with the demands of femininity?Research has focused on the ways media and cultural messages victimize young women, but little attention has been paid to the ways they resist these messages. In Pretty in Punk, Lauraine Leblanc examines what happens when girls ignore these cultural messages, parody ideas of beauty, and refuse to play the games of teenage femininity. She explores the origins and development of the punk subculture, the processes by which girls decide to “go punk,” patterns of resistance to gender norms, and tactics girls use to deal with violence and harassment.Pretty in Punk takes readers into the lives of girls living on the margins of contemporary culture. Drawing on interviews with 40 girls and women between the ages of 14-37, Leblanc examines the lives of her subjects, illuminating their forms of rebellion and survival. Pretty in Punk lets readers hear the voices of these women as they describe the ways their constructions of femininity—from black lipstick to slamdancing—allow them to reject damaging cultural messages and build strong identities. The price they pay for resisting femininity can be steep—girls tell of parental rejection, school expulsion, institutionalization, and harassment. Leblanc illuminates punk girls' resistance to adversity, their triumphs over tough challenges, and their work to create individual identities in a masculine world.
Keywords: Family & Relationships / Life Stages / Adolescence; Social Science / Popular Culture; Social Science / Women's Studies